(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Today, we cannot imagine our life: private or work without innovative technics because they provide us endless opportunities to expand our horizons of knowledge in language teaching and learning. Consequently, it improves our experience and theoretical thoughts what we are willing to get from them. English is being foremost in all subjects of learning, educate lots of people. Moreover, lots of people are seeking ways to acquire engineering English at present. This article highlights the features of innovative technology and its essence in education, especially in language learning.